(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research aims to know the impact of leadership integrity as explanatory variable including its dimensions (courage, asceticism, justice, rationality, and humanity) on organizational conflict as responding variable. This research depended on the descriptive- constructive approach through the responses of a sample of (79) employees from (Real Estate Office of The State) in Al-Najaf province. The analyzing of the study done by using (Smart PLS) program to calculate (R2, t, p). Many results concluded and one of them, there is significant impact correlation of the leadership integrity on organizational conflict. There are many suggestions have been reached depending on the results reached and one of them is the necessity of developing and benefit from using leadership integrity approach in order to face any negative organizational conflicts through the strategies and methods which reinforce its achievement and adaptation in the work environment that touch the spirit, culture and values of employees.